2022
DOI: 10.3138/cjpe.70805
|View full text |Cite
|
Sign up to set email alerts
|

Planning the Evaluation of Patient Engagement in the PriCare Research Program

Abstract: The involvement of patients, their families, or their representatives is becomingincreasingly common in health-care research. However, theoretical justif cationof patient engagement (PE) and consistent guidance on how to include patients askey stakeholders on research teams are still lacking. Tis paper describes how the Pri-Care group integrates PE into its program’s governance structure and uses a programlogic perspective to engage patients in the planning phases of a research study basedon resources, process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Danish et al's 29 study on the description of the PriCARE ‘program logic perspective’ identified resources, processes and relationships (rather than context, resources, activities and outcomes). Their study supported the importance of a governance structure that integrates patient partnerships early in the programme to facilitate the evaluation and continuous improvement of PE.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Danish et al's 29 study on the description of the PriCARE ‘program logic perspective’ identified resources, processes and relationships (rather than context, resources, activities and outcomes). Their study supported the importance of a governance structure that integrates patient partnerships early in the programme to facilitate the evaluation and continuous improvement of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Their study supported the importance of a governance structure that integrates patient partnerships early in the programme to facilitate the evaluation and continuous improvement of PE. The authors argue that providing a framework for documenting, categorizing, monitoring and improving PE activities throughout the various phases of a research project strengthens PE evaluation capacity 29 . Boivin et al 8 ,p.2 concur in an editorial on the importance of rigorous evaluation of the patient and public involvement in research, stating that there is a need to ensure that PE ‘becomes an integral, robustly conducted, and well‐resourced component of research, not a last minute add on’.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations